Qt for symbian - Fitzek, Frank H. P; Fitzek, Frank H. P; Mikkonen, Tommi; Torp, Tony (WILEY, 2010)
Qt for Symbian takes a unique look at this cutting-edge programming environment. Step-by-step it explains Qt in an easy to access fashion, using simple examples throughout. A bible for all beginners it covers topics such as:Installing the developer platform / SDKExplaining the basic Qt environmentThe extension of Qt for Symbian modulesCommunicationSensorsEtcSimple examples for Qt for SymbianThis Nokia-endorsed primer written by developers involved in the new release of Qt will ultimately save you costs, development resources, and will help you get to market faster!